PENGARUH TOTAL ASET DAN DANA PIHAK KETIGA TERHADAP PEMBIAYAAN PADA BANK MUAMALAT INDONESIA TAHUN 2018 SAMPAI DENGAN 2022 - Aminullah Marlis Tanjung; Aswin Fahmi D; M. Radiansyah; M. Guffar Harahap (CV. Barokah Publsiher, 2023)
This study aims to determine and analyze the effect of Total Assets and Third Party Funds on Financing at Bank Muamalat Indonesia from 2018 in the first quarter to 2022 in the third quarter. The data used is the published financial statements of Bank Muamalat Indonesia. The method of analysis in this study is the associative method, with classical testing, as well as statistical analysis, namely multiple linear regression analysis. The results of the analysis using the statistical t test with significant (α) = 0.05 using the sig value of the SPSS output obtained the significance value of each independent variable Total Assets (0.00) and DPK (0.655) Results of analysis with the F test with significance (α) = 0.05 obtained a significance of 0.000. This value is not greater than a significance value of 0.05 and this indicates that there is a significant relationship between Total Assets and Third Party Funds towards simultaneous financing.